Consuming catastrophe : mass culture in America's decade of disaster - Recuber, Timothy, 1978- (Temple University Press, 2016)
"Horrified, saddened, and angered: That was the American people's reaction to the 9/11 attacks, Hurricane Katrina, the Virginia Tech shootings, and the 2008 financial crisis. Timothy Recuber presents a unique and provocative look at how these four very different disasters took a similar path through public consciousness. He explores the myriad ways we engage with and negotiate our feelings about disasters and tragedies--from omnipresent media broadcasts to relief fund efforts and promises to 'Never Forget.' Recuber explains how a specific and 'real' kind of emotional connection to the victims becomes a crucial element in the creation, use, and consumption of mass mediation of disasters. He links this to the concept of 'empathetic hedonism, ' or the desire to understand or feel the suffering of others."--Provided by publisher